2021
DOI: 10.1038/s41598-021-96225-7
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomographic angiography study of perfusion recovery after surgical lowering of intraocular pressure

Abstract: We investigated the time and location of retinal perfusion recovery after surgical intraocular pressure (IOP) lowering in glaucoma by using optical coherent tomography angiography (OCTA). Seventeen patients were analyzed. The 4.5 × 4.5-mm OCTA scans centered on the disc were performed preoperatively and postoperatively at 6 weeks, 3 months, and 6 months. The peripapillary retinal nerve fiber layer (NFL) thickness, NFL plexus capillary density (NFLP-CD) and visual field (VF) were measured overall and in 8 corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
0
12
1
Order By: Relevance
“…This would be consistent with the NFLP being the most sensitive plexus to show decreased perfusion in glaucoma patients. 38 40 By contrast, we have observed that the rat NFL is much thinner and does not have a specific NFLP. 12 In addition, major retinal vessels, as well as the entire SVP, are located anterior to the NFL.…”
Section: Discussioncontrasting
confidence: 65%
“…This would be consistent with the NFLP being the most sensitive plexus to show decreased perfusion in glaucoma patients. 38 40 By contrast, we have observed that the rat NFL is much thinner and does not have a specific NFLP. 12 In addition, major retinal vessels, as well as the entire SVP, are located anterior to the NFL.…”
Section: Discussioncontrasting
confidence: 65%
“…A negative effect of elevated IOP on retinal microcirculation was also found in an animal model [ 21 ]. When IOP decreased after glaucoma surgery, a significant increase in VD in the lamina cribrosa and in the peripapillary retinal nerve fibre layer plexus capillary density was found [ 22 , 23 ]. Peripapillary and macular VD also significantly increased in individuals with high IOP after medical IOP reduction [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the decreased IOP in glaucoma patients increases perfusion of retinal microcirculation. Liu L. et al (2021) found that the post-operative IOP decreased by an average of 5.3 mmHg, and that the perfusion of the retinal microcirculation of para-optic disk was significantly improved. Hence, changes in IOP could affect the perfusion of the retinal microcirculation of para-optic disk.…”
Section: Discussionmentioning
confidence: 93%